FLASH CARDS SEBAGAI MEDIA PEMBELAJARAN KREATIF PENGENALAN BAHASA JAWA KRAMA PADA ANAK BERKEBUTUHAN KHUSUS YANG BERKATEGORI TUNAGRAHITA DI KABUPATEN KARANGANYAR - Kenfitria Diah Wijayanti; Dyah Padmaningsih (LITERASI: Indonesian Journal of Humanities, 2014)
This article aims to get an overview of the characteristics of the Javanese language used by students with mental retardation and to explain the effectiveness of the Javanese language learning in children with mental retardation using flash cards media. This type of qualitative research focused on a phenomenon studied in depth. The population sample of this study included 30 students of the SDLBN Cangakan Karanganyar. The characteristicts of Javanese language use among the mentally disabled children are: (1) sound imitation, (2) a foreign vocabulary, (3) first spoken language, (4) foreign language, (5) the answers to vocabulary, and (6) the pronunciation of syllables upside down. The application of flash media cards yielded the following results. In Phase I it is obtained an average performance of 50.3%, 59.3% in Phase II, and 61.3 % in Phase III. Keywords: learning media, flash cards, tunagrahita